Applying Science Process Skills in Understanding Chemical Equilibrium Through Experiment - Friska Purba; Debora Suryani Sitinjak; Kelly Sinaga (Jurnal Akademika Kimia, 2021)
Students from Teachers College coming from various regions causes variations in the cognitive, affective, and psychomotor level. Some of them have a difficulty that leads to misconception in understanding the content in chemistry, particularly on chemical equilibrium. One of the ways to comprehend that content is by conducting experiments. This study aims to apply science process skills in understanding chemical equilibrium through the experiment method. This research also helps students in their experiments in which their ability is shaped to reach the level of application. Through experiment method, science process skill will develop and give a good response in giving action both in cognitive comprehension and ineffective as well as psychomotor level. The research method used is pre-experimental with a One-Group Pre-Post test Design.  The result showed N-gain was 0.7, which classified high categories and science process skills showed good categories. The final result of this research was that students would be able to understand chemical equilibrium better by applying science process skills with an experiment.